2018
DOI: 10.2478/sues-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance at National Level

Abstract: Throughout this study, we have shown the influence factors generating a significant impact on taxpayers’ tax behavior. We also analyzed the literature in the field, and the categories of factors that have a significant influence. Consequently, we have assigned a macroeconomic indicator in Romania, in an attempt to quantify the factors of influence. In this regard, we have built an econometric model of multifactorial regression and we have determined the impact of some elements such as: poverty, labor productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Meanwhile, Opreț et al (2017) analyze the importance of accounting information for increasing fiscal policy transparency and enhancing the combat against tax fraud, and reducing the level of tax evasion. Brezeanu et al (2018) suggest that there can be identified a strong negative correlation revealed by the econometrical manifested between tax compliance and labor productivity, financial capacity, and a positive relationship with GDP per capita.…”
Section: Introduction and Literature Reviewmentioning
confidence: 92%
“…Meanwhile, Opreț et al (2017) analyze the importance of accounting information for increasing fiscal policy transparency and enhancing the combat against tax fraud, and reducing the level of tax evasion. Brezeanu et al (2018) suggest that there can be identified a strong negative correlation revealed by the econometrical manifested between tax compliance and labor productivity, financial capacity, and a positive relationship with GDP per capita.…”
Section: Introduction and Literature Reviewmentioning
confidence: 92%
“…Levenko and Staehr (2021) conclude that tax compliance is important if it is associated with aspects such as social norms, personal norms, and customs. Brezeanu et al (2018) analyze tax compliance at the Romanian national level land come to the conclusion that through multiple regressions there can be identified two situations: first, fiscal behavior is negatively correlated with labor productivity and financial capacity; second, a positive correlation is manifested between gross domestic product per capita and the taxpayer's behavior.…”
Section: Tax Compliance Agendamentioning
confidence: 99%
“…Power and trust influence tax compliance. Regarding the trust variable, there is a negative link between tax compliance and taxpayers' confidence in state authorities (Brezeanu, Dumiter, Ghiur, & Todor, 2018). Trust in the government influences tax compliance (Jimenez & Iyer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%